RABIES OUTBREAK IN A NOMADIC COMMUNITY IN RINGIMAWA VILLAGE, KANO STATE, NIGERIA: A CASE REPORT - Habibu, Shaarani Musa; Bakari, Ado Hassan; Nagoma, Auwal Usman; Hanga, Aminu Bello; Aminu, Aishatu Ibrahim; Ibrahim, Idris Kyauta; Garba, Aliyu; Dambazau, Z. B. (FUDMA JOURNAL OF SCIENCES, 2025)
Rabies remains a significant public health concern in Nigeria, particularly among rural and nomadic populations with limited access to veterinary and healthcare services. This case study investigates a rabies outbreak that occurred in Ringimawa, a nomadic community in Garun Malam Local Government Area of Kano State. The outbreak was triggered by the bite of a rabid dog, which led to multiple exposures among animals. A total of 4 cattle and Five dogs were involved in the outbreak with 75% and 100% fatality in each dog and cattle species respectively. Brain tissues and saliva samples from the cows tested positive using chromatographic lateral flow assay (Shenzen Lvshiyuaun Biotecnology) and further confirmed positive by Florescent antibody assay by a reference Laboratory. In response, a rapid multi-sectoral team was mobilized to conduct emergency vaccination of dogs, community sensitization, and contact tracing. The outbreak underscores the urgent need for a One Health approach to rabies control, emphasizing improved access to veterinary and public health interventions, especially in underserved nomadic communities. Strengthening community-based surveillance, promoting responsible dog ownership, and integrating nomads into national rabies elimination programs are essential to achieving the global target of zero human deaths from dog-mediated rabies by 2030.
Keywords: Rabies; Outbreak; Cattle; Dog